Sistem Pakar Dalam Menganalisis Tingkat Akurasi Keparahan Penyakit Erosi Gigi Menggunakan Metode Certainty Factor - Dwi Narulita; Y Yuhandri (Jurnal Informasi dan Teknologi, 2021)
The body parts that also need to be kept healthy are the teeth and mouth. Because if the part is experiencing problems, it can be ascertained that the body is in a serious problem. Tooth erosion is the most obvious form of impact when this problem is underestimated. Tooth erosion is damage that occurs by involving the hard tissues of the teeth by chemical processes that reduce the function of the teeth themselves. This situation is caused by the lack of a person having their teeth checked by a dentist due to a lack of awareness and attention to dental health, the high cost to go for a consultation, the long queues making it less comfortable and comfortable to wait. Therefore, this study aims to create a system that can represent the expertise of the dentist himself so that whenever and wherever the public can easily consult about dental health. The data used in this study involved a history of patient consultations at the Drg Florentina clinic where 10 patient data with the same diagnosis were taken as samples. The results of this study the system can identify the severity of dental erosion as much as 80%. Therefore, this research can be used as a reference for further research with the same theme.